Pengaruh Tummy Time Exsercise terhadap Peningkatan Motorik Bayi 3 Bulan - 6 Bulan di Klinik Physioroom Medan Selayang - Riani Baiduri Siregar; Heri Saputra; Rudi Purwana; Ani Ramahdhani (Lembaga Pengembangan Kinerja Dosen, 2025)
Motor development in infants is a crucial process that occurs gradually and follows the principles of age-appropriate development. Each fundamental motor stage—such as tummy time, rolling over, sitting, crawling, standing, and walking—must be passed through sequentially to ensure optimal motor concept development. Skipping or insufficient stimulation of these stages may lead to difficulties in understanding functional body movements. One of the main causes of delayed motor development includes a lack of motor stimulation time, overly restrictive parental supervision, and low levels of motivation and stimulation provided to the child. Tummy time, or placing the baby in a prone position while awake, is a proven effective form of motor stimulation that supports the development of the baby’s neck, back, and arm muscles. This activity also assists infants in reaching subsequent developmental milestones such as rolling over and crawling. This Community Service Program (PkM) was conducted at the Physioroom Clinic and was attended by 15 mothers with infants aged 3 to 6 months. The objective of the program was to enhance mothers’ knowledge regarding the importance of tummy time in supporting infant motor development. The program's implementation included educational sessions, tummy time practice demonstrations, group discussions, and interactive Q&A sessions. To measure the increase in participant knowledge, a pre-test and post-test were administered before and after the activity.The results of this PkM activity showed an increase in the average knowledge score from 6.4 in the pre-test to 8.6 in the post-test. This improvement demonstrates the program’s effectiveness in educating mothers about the benefits of tummy time for infant motor development. It is hoped that the mothers will consistently apply this stimulation at home to optimally support their children's growth and development.